Research Trends in the Last 3 years Related to Distance Education : A Bibliometric Study - Dewi Andriyani; Susy Puspitasari; Titi Chandrawati; Syahrul Ramadhan (Jurnal Paedagogy, 2023)
This study aims to analyze the research trends related to distance education over the past three years by examining the publication patterns and key topics within the field. This study used a quantitative descriptive research approach with a bibliometric method. Data was collected through the Scopus database with the keyword "Distance learning" by searching for journals based on keywords, article titles, and abstracts with the condition of publications in 2020-2022. The software used in data analysis in this study was the Bibliometrix R-Package, which was part of R-Studio. A total of 1936 articles were found and analyzed. The study results showed that the number of articles related to distance education has been increasing each year, with a growing trend from 2020 to 2022. The study analyzed the top journals, affiliations, and countries publishing articles and identified the most productive authors and relevant affiliations. The trend topics discussed were social media, distance learning, and learning analytics, with new topics emerging in 2021, such as university students, motivation, and Covid-19. Theme classifications were divided into two, connected by blue and red lines. The study also identified future research opportunities using a thematic map.